COMPARISON OF FRICTION WELD STRENGTH ACROSS DIFFERENT MATERIALS AND SPEEDS (International Journal of Food and Nutritional Sciences, 2022)
ABSTRACT: The solid-state joining process known as friction welding is capable of fusing metals that are either very similar to one another or quite dissimilar from one another for the most part. This method of welding is utilized in a variety of industries, including aviation, undersea engineering, the automobile industry, and heavy duty manufacturing, among others. Researchers in this field have ranked the strength of friction-welded connections made between a variety of metals, including stainless steel to stainless steel, mild steel to mild steel, and mild steel to mild steel. These connections were made between metals that were both comparable and dissimilar from one another. Metals that were chemically associated with one another were joined together with the help of these bonds.